Computed tomography scan in the evaluation of patients with stroke - Chhetri, PK; Raut, S (Journal of College of Medical Sciences-Nepal, 2012)
Cerebrovascular accident is a frequent cause of death and disability in most parts of the globe. The incidence of cerebrovascular diseases increases with age and the number of strokes is projected to increase as the elderly population grows. This study was undertaken to determine the type of stroke and also to relate the risks factors associated with stroke. Hundred consecutive patients presenting with stroke in the emergency department / neurology clinic were subjected to computed tomography scan of the brain. Sixty – four patients had ischemic infarct and 36 had intracranial hemorrhage which included 2 patients with subarachnoid hemorrhage and 1 with underlying cavernous angioma. Ischemic stroke was thus commoner than hemorrhagic stroke. Previous infarct or lacunes were noted in 25 % of the patients presenting with stroke. Risk factors were present in most (77 %) of the patients presenting with stroke. Among the various risk factors, the single most common was smoking seen in 38 cases, followed by hypertension in 28 cases, obesity in 8 cases and diabetes in 3 cases. Twenty- one patients had multiple combinations of the above risk factors. Among the multiple risk factors, combination of alcohol and smoking was the commonest seen in 11 cases, followed by hypertension and obesity in 8 cases and alcohol with obesity in 2 cases. Change in lifestyle and eating habits may thus help reduce the incidence of stroke. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 24-31 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6834